Meteoroid streams and their parent bodies - Jopek, Tadeusz J. (Memorie della Societa Astronomica Italiana, 2011)
Various points concerning meteoroid streams and their parent comets and asteroids are presented. The first connection between meteoroids and comets, among others, were established by G.V. Schiaparelli 150 years ago. The first computer search for meteoroid streams was made by Southworth and Hawkins 50 years ago. Since that time many investigators have been studied the problem of cometary and asteroidal origin of meteoroid streams. Many results have been established. In this study we made the most extensive search for streams and their parent bodies amongst photographic meteoroids, comets and minor planets. We used two D- distance functions and rigorous cluster analysis approach. The well known results have been confirmed -- several major streams and their parents have been identified. Also we found ten associations consisting mainly of the near Earth asteroids. The obtained results do not allow us to make a final conclusions about the genetic reality or the origin of these associations.
Keywords: meteors; parent bodies of the meteoroid streams; meteoroid; meteoroid streams; asteroidal streams; stream searching techniques